Srpski Srpski - Zec, Marina (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
In a global, highly networked world, the creation of media policies at the national level is becoming obsolete and the need to create supranational guidelines and recommendations in the field of media policy is evolving. This study focuses on the comparative analysis of the “Strategy for the development of the public information system in the Republic of Serbia for the period 2020-2025. year“ and the UNESCO manual “Media and Information Literacy: Policy and Strategy Guidelines“. This paper aims to assess whether and to what extent the "Strategy for the development of the public information system in the Republic of Serbia for the period 2020-2025. year” followed the recommendations of the UNESCO handbook. The theoretical framework of the paper is represented by theories of media policy in global discourse and definitions of media literacy by James Potter and Tibor Coltay, and the empirical part of the paper is based on desk research, content analysis, and comparative analysis. The general conclusion of the paper is that although the Media Strategy indicates a basic understanding of the need to develop media literacy, the measures prescribed by the Media Strategy are broadly defined, do not have specific indicators, and leave room for free interpretation of the functionality of these measures, meaning they are not written according to UNESCO handbook guidelines.
Keywords: Srpski